Stabilitas dan Risiko Bank: Dampak Capital Adequacy Ratio dan Non Performing Loan terhadap Profitabilitas melalui Loan to Deposit Ratio - Salmi Yuniar Bahri; Slamet Riyadi (Lembaga Pengembangan Kinerja Dosen, 2026)
The objective of this study is to describe and analyze the effect of Capital Adequacy Ratio (CAR) and Non-Performing Loan (NPL) on the profitability of conventional banks listed on the Indonesia Stock Exchange, with Loan to Deposit Ratio (LDR) serving as an intervening variable, within the context of bank stability and risk. This study employs a quantitative research design with an explanatory approach. The population of this research includes all conventional banks listed on the Indonesia Stock Exchange during the period 2017 to 2025, totaling 37 banks. The sampling technique used is purposive sampling, resulting in a sample of 15 banks, including Bank Negara Indonesia (Persero) Tbk, Bank Rakyat Indonesia (Persero) Tbk, Bank Tabungan Negara (Persero) Tbk, Bank Mandiri (Persero) Tbk, Bank CIMB Niaga Tbk, Bank BTPN Tbk, Bank Pan Indonesia Tbk, Bank Maybank Indonesia Tbk, Bank Danamon Indonesia Tbk, Bank China Construction Bank Indonesia, Bank Woori Saudara Indonesia 1, Bank Maspion Indonesia Tbk, Bank Capital Indonesia Tbk, Bank KB Bukopin Tbk, and Bank Syariah Mandiri. The data analysis method employed is Partial Least Squares (PLS) with the assistance of SmartPLS 3.0 software. The results indicate that CAR has a negative but insignificant effect on LDR, while NPL has a negative and significant effect on LDR. Furthermore, both CAR and NPL have positive but insignificant effects on profitability, and the path analysis demonstrates that LDR cannot serve as an intervening variable in the relationship between CAR or NPL and the profitability of the sampled conventional banks.